ACCEPTABILITY TEST OF PROCESSED TUBER PRODUCTS AS A LOCAL FOOD ALTERNATIVE - Siti Nurlani Harahap; Fitri Dian Nila Sari; Riani Sari Sembiring (INJOSEDU: International Journal of Social and Education, 2026)
The purpose of this study is to determine the level of acceptance of panellists towards processed sweet potato–potato patties and purple sweet potato onde-onde through organoleptic tests. This research is an experiment with a completely randomized design (CRD) involving 15 trained panelists from the academic community of Nahdlatul Ulama University of North Sumatra. The research method includes product development with various formulations, followed by a hedonic test on the attributes of taste, color, aroma, and texture using a numerical scale of 1–5. The data from the panelists' evaluations were analyzed descriptively to determine the most preferred treatment. Research results show that for perkedel products, formulation P0 (100% sweet potato, 0% potato) obtained the highest scores in all organoleptic attributes (taste 3.53; color 3.67; aroma 3.47; texture 3.67), making it the formulation most preferred by the panelists. In purple sweet potato onde-onde products, the most preferred taste attribute was found in treatment M2 (50% glutinous rice flour, 50% purple sweet potato) and M4 (100% purple sweet potato), whereas the best color, aroma, and texture were obtained in treatment M3 (25% glutinous rice flour, 75% purple sweet potato). The use of yellow sweet potatoes in full produces fritters with the best sensory quality, Meanwhile, the substitution of purple sweet potato in a balanced or dominant proportion can increase panelists' acceptance of onde-onde.